Heteragrion itacolomii sp. nov. (Odonata: Zygoptera: Heteragrionidae) from Itacolomi State Park, Ouro Preto, Minas Gerais, Brazil - Ávila Júnior, Walter F.; Lencioni, Frederico A. A.; Carneiro, Marco Antônio A. (Zootaxa, 2020)
Heteragrion itacolomii sp. nov. (♂ holotype: Brazil, Minas Gerais, Ouro Preto, Parque Estadual do Itacolomi, Trilha da Lagoa, 1350m, 23-xii-2018, 20º25’57”S, 43º30’27”W; and ♀ allotype, same data as holotype, but collected in tandem 20-iii-2019, deposited in ABMM – CCT/UFMG collection) is described and illustrated. The new species is similar to H. tiradentense Machado & Bedê, 2006, H. muryense Costa & Santos, 2000 and H. mantiqueirae Machado, 2006, based on coloration of the thorax and has cerci similar to those of H. freddiemercuryi Lencioni, 2013. It belongs to Group A and differs from other congeners by the morphology of the ventral expansion and the medial process of the cerci in males. Information about the intersternite of the single female specimen is also provided.